Magmatic emplacement of northwestern Geece ophiolites - BRUNN, J. H.; ARGYRIADIS, I.; BRAUD, J. (Bulletin of the Geological Society of Greece, 2002)
New field observations reinforce the interpretation that was admitted from 1956 to 1970 according to which the ophiolites of Northwestern Greece were generated and emplaced as a massive submarine flow of mantelle magma which had risen through the opening of an orogenic rift. As it opened, the still narrow rift left out submarin tuffs and lavas (pillows) which have been found in different places under the basal peridotites of ophiolitic suits.